PENTINGNYA POSBINDU KELILING DALAM MENDETEKSI PENYAKIT TIDAK MENULAR DI RW. 05, KELURAHAN KEDAUNG KALIANGKE - Firmansyah, Yohanes; Ginting, Desi Natalia; Su, Ernawati; Sylvana, Yana; Chau, Welhan; Setyati, Pinka Nurashri (Universitas Tarumanagara, 2021)
Non-communicable diseases (NCD) especially hypertension and cardiovascular diseases have become the highest cause of death in the world with a mortality rate of nine million deaths (44% of all non-communicable disease deaths and 31% of all global causes of death). The purpose of this study was to determine the effectiveness of the Mobilization in Utilization Of Community Participation (Mobilization POSBINDU) activities to detect risk factor and early diagnosis of non-communicable diseases (NCD) especially hypertension. Methods: Cross-sectional method was applied to the society in Sector 5th Kedaung Kaliangke District, the variables in this research were tested using the chi-square test, Independent T-test, and Mann Whitney test. Results: 40 respondents who met the study criteria. There were no differences in the incidence of hypertension (55% vs 60%; p-value: 1,000), average of SBP (138.25 (24.36) vs 144.45 (20.24); p-value: 0.394) and average of DBP (85 (68 -132) vs 83 (58 - 105) mmHg; p-value: 0.369) between 2 groups of people who have never been to Posbindu with those who are routinely to Posbindu. There are still many people who have not been screened from Posbindu activities and still urgently need to Mobilization in Utilization Of Community Participation Program (Posbindu Linpung) to get more people for early detection of NCD. Conclusion: Posbindu Linpung has proven effective in finding new cases of hypertension in the community. This is proven by the fact that there is no difference in the mean blood pressure of a population group that has never been screened with a group that routinely does a screening. Keywords: mobilization posbindu ; routinely ; hypertension AbstrakPenyakit tidak menular (PTM) khususnya hipertensi dan penyakit kardiovaskuler telah menjadi penyebab kematian tertinggi di dunia dengan angka mortalitas sembilan juta kematian (44% dari semua kematian penyakit tidak menular dan 31% dari semua penyebab kematian global). Tujuan penelitian untuk mengetahui efektivitas dari kegiatan Posbindu PTM Keliling Kampung dalam surveilans faktor risiko dan deteksi dini PTM. Metode: Potong lintang pada masyarakat RW 05 Kelurahan Kedaung Kaliangke, serta data penelitian di uji dengan uji Chi-square , Independent T-Test, dan Mann Whitney. Hasil Penelitian: 40 responden yang memenuhi kriteria penelitian. Tidak didapatkan perbedaan kejadian hipertensi (55% vs 60% ; p-value : 1,000), rata-rata TDS (138,25 (24,36) mmHg vs 144,45 (20,24) mmHg ; p-value : 0,394) dan rata-rata TDD (85 (68 - 132) mmHg vs 83 (58 - 105) mmHg ; p-value : 0,369) yang tidak bermakna antar 2 kelompok masyarakat yang tidak pernah ke posbindu dengan yang rutin ke posbindu. Hal ini membuktikan bahwa masih banyak masyarakat yang belum terskrining dari kegiatan Posbindu dan masih sangat memerlukan Posbindu Linpung untuk menjaring lebih banyak masyarakat untuk deteksi dini PTM. Kesimpulan: Posbindu Linpung terbukti efektif dalam menjaring kasus baru penyakit tidak menular (hipertensi dan obesitas) yang berada dalam masyarakat. Hal ini terbukti dari tidak terdapat perbedaan rerata tekanan darah dari kelompok populasi yang tidak pernah melakukan skrining dengan kelompok yang rutin melakukan skrining.